The influence of task technology fit e-learning as training media on employee performance at PT XYZ - Zuliarni, Sri; Hendian, Suci (Social Sciences Insights Journal, 2025)
The E-learning Brismart application is a system designed to enhance the quality and performance of employees at PT. XYZ to realize the company's goal of becoming The Most Valuable Banking Group in Southeast Asia and Champion Financial Inclusion. This study aims to analyze the effect of E-learning Brismart as a training medium intended for workers at PT. XYZ is using the Task Technology Fit (TTF) theory evaluation model. The research activities used questionnaires as a quantitative approach for PT. XYZ Kc Batam Nagoya employees. The analysis results show that E-learning Brismart affects employee performance at PT. XYZ Batam Nagoya Branch Office, as evidenced by the positive correlation between variables.